Thyroid Dysfunction In Patient With Nephrotic Syndrome (TAJ: Journal of Teachers Association, 2018)
A large amount of protein is lost in urine along with thyroid hormones and hormone binding proteins in nephrotic syndrome (NS). This hormone loss may lead to low T4, T3 and sometimes high TSH level and often to be associated with subclinical or overt hypothyroidism. This study was done to assess thyroid dysfunction in patients with NS and to correlate thyroid hormones with albumin level of those subjects. Forty diagnosed patients of idiopathic NS and same number of age matched healthy control were selected in this study. Thyroid status was evaluated in all the subjects. In patients with NS mean (± SD) of T4, T3 and TSH were 39.34 (±29.49), 1.05 (±0.83) and 11.34 (±18.15) respectively. Mean (±SD) of T4, T3 and TSH in healthy control were 83.34 (±27.23), 2.04 (±0.70) and 2.73 (±1.79) respectively. Mean serum total T4 and T3 of patients with NS were found to be significantly lower (t= -6.935, df= 78, p